The Impact of Scenario Planning in Managing Complexity Strategy: The Mediating Role of Strategic Flexibility: An Applied Study of the Opinions of a Sample of Managers of the General Company for Construction Contracting in Baghdad - Alhamdany, Saba Noori Alhamdany; Hamed, Suhair Adel Hamed; Abou Essa, Emad aldeen; Naas, Said Ali (Jordan Journal of Business Administration, 2024)
The aim of this study was to examine the impact of scenario planning on managing complexity strategy and investigate whether strategic flexibility acts as a mediator between scenario planning and complexity strategy. The study was conducted on a sample of 75 employees from the General Company for Construction Contracting in Baghdad out of a study population of 400 employees. The data was collected through a questionnaire that was distributed to various department managers in the company. The study aimed to test several hypotheses and sub-hypotheses related to the relationship between the study variables. The study results indicate that there is a positive relationship between scenario planning and complexity strategy, although it is only partial. The study also found that strategic flexibility partially mediates the relationship between scenario planning and complexity strategy. Therefore, scenario planning can enhance complexity strategy, but strategic flexibility plays a crucial role in mediating this relationship. The study recommends that cognitive skills of the scenario drafting team should be developed, particularly in the areas of induction and deduction, to facilitate the identification of pre-determined factors and the formulation of flexible assumptions for scenarios. Additionally, the study suggests expanding the scope of competitive flexibility and productivity in the face of intense betting, globalization and openness, as well as achieving a competitive position aligned with the company's objectives based on the structure of complexity theory.